Restoration of Type I Interferon Expression by Heme and Related Tetrapyrroles Through Inhibition of NS3/4A Protease - Zhu, Zhaowen (J Infect Dis, 2013)
Background. Tetrapyrrole substrates and products of heme oxygenase are potent inhibitors of hepatitis C virus (HCV) replication. It is not clear whether this occurs through primary induction of type I interferon (IFN), inhibition of viral NS3/4A protease, or a combination of these mechanisms. We studied the antiviral actions of tetrapyrroles and their potential influence on type I IFN induction. Methods. The effects of tetrapyrrole on NS3/4A protease activity and type I IFN induction were assessed in HCV-permissive cells, replicons, or human embryonic kidney (HEK) 293 cells transfected with NS3/4A protease. Activation of innate immune signaling was determined after transfection of double-strand surrogate nucleic acid antigens or infection with defined sequence HCV cell culture (HCVcc) RNA. Results. Tetrapyrroles failed to directly induce IFN expression at concentrations that inhibited HCV replication and NS3/4A protease activity. However, they potently restored IFN induction after attenuation with NS3/4A protease, a process accompanied by preservation of the adapter protein, mitochondrial antiviral signaling protein, nuclear localization of IFN regulatory factor 3, and augmentation of IFN-stimulated gene products. Conclusions. Tetrapyrroles do not directly induce IFN, but they dramatically restore type I IFN signaling pathway after attenuation with NS3/4A protease. They show immunomodulatory as well as antiprotease activity and may be useful for treatment of HCV infection.